2018
DOI: 10.1038/s41379-018-0097-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-L1/PD-1 in lymphoepithelioma-like carcinoma of the thymus

Abstract: Poorly differentiated non-keratinizing squamous cell carcinoma of the thymus, also known as lymphoepithelioma-like carcinoma, is a rare primary malignant neoplasm of thymic origin. The mainstay of treatment for these tumors is surgical and they tend to respond poorly to chemotherapy. The checkpoint programmed cell death ligand-1 protein (PD-L1) bound to its receptor (PD-1) has been demonstrated to be an important therapeutic target for many different tumors. Expression of PD-L1/PD-1 in lymphoepithelioma-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Consistent with our findings, investigations on patients with lymphoepithelioma-like carcinoma of the thymus have also revealed the absence of actionable genes as well as the detection of various degrees of membranous PD-L1 staining in their cohort (total: 71.4%, 15/21; high expression (>50% of tumor cells): 48%; low expression (<50% of tumor cells): 25%) [51,52]. Moreover, they have observed that the patients with PD-L1 expression contained abundant lymphocytes in the stroma, despite the lack of EBV positivity [52]. In contrast to their report, we did not find a correlation between the PD-L1 expression and extent of lymphocytic infiltration in our cohort (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, investigations on patients with lymphoepithelioma-like carcinoma of the thymus have also revealed the absence of actionable genes as well as the detection of various degrees of membranous PD-L1 staining in their cohort (total: 71.4%, 15/21; high expression (>50% of tumor cells): 48%; low expression (<50% of tumor cells): 25%) [51,52]. Moreover, they have observed that the patients with PD-L1 expression contained abundant lymphocytes in the stroma, despite the lack of EBV positivity [52]. In contrast to their report, we did not find a correlation between the PD-L1 expression and extent of lymphocytic infiltration in our cohort (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 90%
“…evidence of elevated expression in LELCs, as in our patient, which may underlie potential ICI effectiveness as in other specific tumor subtypes. 17 In addition to the above histologic findings that could suggest plausible benefit from ICIs in LEL-HCC, genomic comparisons between LEL-HCC and HCC have revealed mutational differences that suggest LEL-HCC may be more immunogenic and therefore potentially more susceptible to ICIs. Whole exome sequencing comparisons between conventional HCC and LEL-HCC have identified decreased overall nucleotide variants in specific genes of the Wnt/β-catenin and Notch signaling pathways as well as focal amplification of chromosome 11q13.3 in LEL-HCC.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, although PD-L1 tumor expression has not been predictive of benefit of ICIs in HCC, there is evidence of elevated expression in LELCs, as in our patient, which may underlie potential ICI effectiveness as in other specific tumor subtypes. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Data from the Cancer Genome Atlas and Foundation Medicine indicated a low tumor mutation burden in thymomas and thymic carcinomas; only 6% of carcinoma cases had >10 mutations/Mb and 3% had >20 mutations/Mb (Figure 2) [13,15]. [30] TMA, clone 5H1 (intensity high) 65 44 (68%) 4 3 (75%) Arbour et al [31] Slides, clone E1L3 (25% of tumor cells cut off) 12 11 (94%) 11 4 (34%) Yokohama et al [32,33] Slides, EPR1161 (H-score, 20% of tumor cells cut off) 82 44 (54%) 25 20 (80%) Weissferdt [34] Slides, clone E1L3 (5% of tumor cells cut off) 74 47 (64%) 26 14 (54%) Markevski et al [28] Slides, clone SP142 (1% of tumor cells cut off) 38 35 (92%) 8 4 (50%) Wei et al [35] TMA, clone E1L3 (% of cells and intensity) 100 100 (100%: 36% low, 64 high) 69 69 (100%: 64% low, 36% high) Guleria et al [36] TMA, clone SP263 (1-25% of tumor cells cut off) 84 69 (82%) Suster et al [37] TMA, clone SP142 (1-50% of tumour cells cut off) 21 (lymphoepithelioma like histology) 15 (71%: 67% high, 33% low) Tiseo et al [38] TMA, clone E1L3 (H-score, 1% of tumor cells cut off) 87 16 (20%) 25 13 (52%) Bagir et al [39] Slides, clone AM26531AF-N (intensity) 37 21 (57%) 6 4 (67%) Sakane et al [40] Slides…”
Section: Pathogenesis Of Autoimmunity In Thymic Epithelial Tumorsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]; overall, expression of PD-L1 is common in thymomas and thymic carcinomas, and is usually high and intense. In the micro-environment, a large Inhibition of autoimmune regulator leads to release of autoreactive lymphocytes and autoimmune disorders.…”
mentioning
confidence: 99%